DEVELOPING ENGLISH READING MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF SOFTWARE ENGINEERING PROGRAM AT SMKN 9 MEDAN - Chicy Ramadhayanty; Rafika Dewi Nasution (Universitas Negeri Medan, 2021)
The objective of this study was to develop English reading materials based on the students of Software Engineering needs for the eleventh grade students at SMKN 9 Medan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, designing materials, validating, revising (final product). The subject of the study was grade eleventh of SMKN 9 Medan. The data were gathered by conducting interview to English teacher and distributing questionnaire to XI RPL 3 consists of 24 students to get the students’ need. To collect the data of the research, conducting interview to English teacher and two types of questionnaires were used as the instruments. The developed reading materials were validated by two experts which are the average scores for the analytical exposition material (4.65 and 4.7) and for the explanation text (4.65 and 4.6) show that the reading materials are valid and suitable to use for the eleventh grade students of software engineering program. Based on the results of the expert judgment, the developed materials were considered appropriate, which was very good.Key words: Development, Reading Materials, Software Engineering.